RANCANG BANGUN ALAT PENGEPRES EMPING MELINJO (Gnetum gnemon L.) (Disign of Tool for Melinjo Chip Pressing) - Hady Susilo; Achwil Putra Munir; Sumono Sumono (Universitas Sumatera Utara, 2017)
ABSTRACT Melinjo be producing chips is one way to inerease the selling price of mmaterials, namely the pressing process material that is molded into melinjo. The purpose of this research was to design, build, test and analyze the economic value of grains’ chip molder. The parameters observed were effective capacity, percentage of damaged material, organoleptic’s test and economic analysis.Based on this research, it was summarized that the effective capacity of the equipment was 1,71 kg/hour and the damaged material’s percentage was 12%. The color was categorized as 2 (white), the thickness was categorized as 1 (thin) and the plavor was categorized as 2 (medium). Economic analysis was as follows : basic costs for the first to the fifth year was Rp. 4.286,8/kg, Rp. 3,968,21/kg, Rp. 3.862,16/kg, Rp. 3.809,22/kg and Rp. 3.777,53/kg respectively. Break even point (BEP) for the first to fifth year was 289.78 kg/year, 156.22 kg/year, 111.77 kg/year, 89.57 kg/year and 76.29 kg/year respective. Internal rate of return was 45.72%. Keywords : melinjo’s chips, molder, pressing. ABSTRAK Memproduksi melinjo menjadi keripik merupakan salah satu cara untuk meningkatkan harga jual bahan, yaitu dengan proses pengepresan bahan yang dicetak menjadi emping melinjo. Penelitian ini bertujuan untuk merancang, membuat, menguji serta menganalisis nilai ekonomis alat. Paremeter yang diamati yaitu kapasitas efektif alat, persentase bahan rusak, uji organoleptik dan analisi ekonomi. Dari hasil penelitian diperoleh kapasitas efektif alat sebesar 1,71 kg/jam dan persentase bahan rusak sebesar 12%. Organoleptik warna dikategorikan 2 (putih), ketebalan dikategorikan 1 (tipis) dan rasa dikategorikan 2 (sedang). Analisis ekonomi, biaya pokok untuk tahun pertama sampai tahun kelima berturut-turut yaitu Rp. 4.286,8/kg, Rp. 3.968,21/kg, Rp. 3.862,16/kg, Rp. 3.809,22/kg dan Rp. 3.777,53/kg. Nilai titik impas (BEP) untuk tahun pertama sampai tahun kelima sebanyak 289,78 kg/tahun, 156,22 kg/tahun, 111,77 kg/tahun, 89,57 kg/tahun dan 76,29 kg/tahun. Internal rate of return adalah sebesar 45,72%. Kata kunci : emping melinjo, alat pencetak.